Language Style in Novel “ The Chronicles of Narnia : The Lion, The Witch and The Wardrobe” by C. S. Lewis - Wahyuni, Reni; Zaim, M. (English Language and Literature, 2021)
Language style is very important to learn to understand a literary work, because everyone has a different language style. The purpose of this study is to determine the type of language style used by Lewis and the social factors that influence the style of language in the novel. The researcher applies a sociolinguistic approach using Martin Joos' theory which divides five language styles, namely frozen style, formal style, consultative style, relaxed style, and familiar style. In this thesis, qualitative method is used to analyze the problem. The researcher found 46 data of the language style, they are frozen style 8 (17.4%), formal style data 8 (17.4%), consultative style data 9 (19.5%), casual style 17 data (37%), and intimate style 4 (8.7%). The findings also show that there were 52 data from social factors that influence the use of language styles, they are participants 20 (39%), setting 2 (4%), topic 22 (41%), and function 8 (16%). In this study, the most dominant style of language is the casual style, while the social factor that most influences the use of language style in this novel is the topic.